2005
DOI: 10.2169/internalmedicine.44.811
|View full text |Cite
|
Sign up to set email alerts
|

KL-6 and Surfactant Proteins A and D in Serum and Bronchoalveolar Lavage Fluid in Patients with Acute Eosinophilic Pneumonia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Elevated KL-6 levels in bronchoalveolar lavage (BAL) fluid have been demonstrated in pulmonary alveolar proteinosis, hypersensitivity pneumonitis, sarcoidosis, acute respiratory distress syndrome and idiopathic pulmonary fibrosis,22 29 30 and in various ILDs elevated serum KL-6 levels have been correlated with BAL levels 26 27. In adults, 500 U/ml has been suggested as an upper limit of normal for serum levels 21. While not as well defined in children, studies reporting healthy paediatric controls have consistently reported serum KL-6 levels below this cut-off and that these levels do not vary with age 18 20 28 31 – 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated KL-6 levels in bronchoalveolar lavage (BAL) fluid have been demonstrated in pulmonary alveolar proteinosis, hypersensitivity pneumonitis, sarcoidosis, acute respiratory distress syndrome and idiopathic pulmonary fibrosis,22 29 30 and in various ILDs elevated serum KL-6 levels have been correlated with BAL levels 26 27. In adults, 500 U/ml has been suggested as an upper limit of normal for serum levels 21. While not as well defined in children, studies reporting healthy paediatric controls have consistently reported serum KL-6 levels below this cut-off and that these levels do not vary with age 18 20 28 31 – 34.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have demonstrated increased expression of KL-6 on regenerating alveolar cells in patients with various types of ILD, with correspondingly high serum levels 16 17. Such elevated KL-6 levels have also been reported in various forms of chILD,18 while normal levels are seen in asthma, bronchiolitis, pertussis, common viral and bacterial pneumonias, and acute eosinophilic pneumonia 1921. Furthermore, while KL-6 levels have been correlated with disease activity, they do not appear to be affected by steroid therapy 22…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In bronchoalveolar lavage, sterile saline is administered into the bronchoalveolar space and aspirated by syringe. …”
mentioning
confidence: 99%
“…[1][2][3][4][5][6]8) Furthermore, the absolute concentration of albumin itself in BALF may allow characterization of interstitial lung disorders. 9,10) Therefore a sensitive and simple method for determining trace amounts of albumin in BALF is desirable.…”
mentioning
confidence: 99%
“…Recently, it has been found that AEP patients have elevated surfactant protein-A (SP-A) and surfactant protein-D (SP-D) when compared with healthy individuals. 10 Important CT findings include thickening of bronchovascular bundles (in a random anatomic distribution) and pleural effusions. 11 Histologic findings of eosinophilic pneumonia include interstitial and alveolar eosinophilia with diffuse alveolar damage.…”
Section: Discussionmentioning
confidence: 99%